Effect of processing and storage on the colour of plantain and banana products - Adeniji, T.A.; Tenkouano, A. (2008)
Fresh pulp from freshly harvested plantain and chips colour as well as the effect of processing and storage on the colour of plantain and banana hybrids Jlour were investigated. Colour values L* (degree of lightness), a* (degree of redness) and b* (degree of yellowness) were detennined with focus on b* value, which is relevant to the pulp colour in African plantain landraces. Agbagba (38.10) and PITA 17 (37.78) differed significantly (P<0.05)from other cultivars infresh pulp degree of yellowness, b*. The degree of yellawness in plantain chips showed that Agbagba (55.03) dffired signiftcantly (P<0.05) from all the hybrids. Colour degradation was obsemed in Musa flour during storage. PITA 14 flour stored in the illuminated experimental cupboard was significantly higher (P<0.05) compared to flour from other cultivars in the degree of yellowness (16.91) after 90 days of storage. Similarly, flour made from PITA 14, stored in dark compartment, with a mean yellowness of 18.35, after 90 days of storage was signijlcantly dffirent (P<0.05) from other cultivars. Established storage condition is critical to plantain and banana production and their diversified value added products.